Geriatric dosage handbook : including clinical recommendations and monitoring guidelines - Semla, Todd P; Beizer, Judith L; Higbee, Martin D (Hudson, Ohio : Lexi-Comp, 2012)
"This handbook follows a dictionary-like format, with brand and generic drug names alphabetically organized and cross-referenced by page number to the generic drug monograph. Within monographs, geriatric-sensitive information includes content on drug interactions and drug dosing in the elderly, in adults and in patients with renal and/or hepatic impairment."--Back cover
"Updates to this edition include: -- 31 new drug monographs -- New appendix topics: immunization administration recommendations, renal function estimation in adult patients -- Updated appendix content: Depression scales, diabetes mellitus management, adult, immunization recommendations, pressure ulcer treatment -- Updated introductory information: FDA name differentiation project, the use of tall-man letters."--Back cover
Includes bibliographical references and index
Keywords: Drugs -- Dosage -- Handbooks, manuals, etc; Geriatric pharmacology -- Handbooks, manuals, etc; Aged; Pharmaceutical Preparations -- administration & dosage; Drug Interactions; Drug Therapy; Handbooks